Aplikasi Marketplace Penyewaan untuk Koperasi Menggunakan Laravel - Tristiyanto .; Yunda Heningtyas; Hanan Risnawati (Jurnal Komputasi, 2020)
Cooperatives have purpose to prosper their members. Cooperatives are expected to play an active role in raising their standard of living. A cooperative has several types of business units in order to fulfill the purpose, for example rental business. Rental occurs because of short-term and urgent needs of consumers. Rental business has been promoted online but there are a lot of ordering phases done manually. Cooperative needs a rental marketplace application so cooperative can be more productive. This rental marketplace is a web based application and developed using Extreme Programming method which perceptive to user’s need. Laravel framework with PHP programming language was used to build this application. The conclusion of this research is this system is able to facilitate the process of renting goods, providing accurate information about rental goods, and expanding the cooperative business sector.